ANALISIS EVOLUSI GRUP SUNSPOT SPD WATUKASEK UNTUK MEMPEROLEH INDIKATOR KEMUNCULAN FLARE - Nanang Widodo; Nur Aeni; - Sudarji; Ahmad Sodikin; - Marlan (Jurnal Sains Dirgantara, 2006)
In their evolution, sunspot groups change in its number, area, shape and its formation. Proper motion of sunspot group show twist and shear movement. Therefore, we measure the central position it preceding and following parts. The difference of angle between the preceding and following part in the evolution on (n + 1) thand n may indicated that in its evolution the sunspot group have changed the area. We suggest some indications for predicting flare using the maesurement of twist and shear of the spot in a group.